Memahami Sensionalisme dalam Berita Televisi: Perspektif Evolusi Biologi - Gentur Agustinus Naru (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2020)
Although there have been many studies regarding sensationalism on television, there have not been enough studies to explain why sensational news always attracts viewers' attention regardless of space or time difference. Encouraged by this background, this research tries to answer the question,